Evaluation standard and improvement method for multi-column envelope profile in single screw compressors. (June 2020) - Huang, Rui; Chen, Guoqing; Li, Ting; Feng, Quanke
Multi-column envelope profile is the newly proposed engagement pair's profile for single screw compressors. Based on hydrodynamic lubrication theory, a calculation model of the oil film moments for star wheel teeth with multi-column envelope profile was established. In order to balance the total oil film moments of the teeth, a profile evaluation standard and improvement method for the multi-column envelope profile were proposed. Then, the profile for a single screw compressor was optimized. The meshing pair with optimized profile is loaded into a prototype to carry out the running test. Results show that the optimization method improves the wear resistance of the star wheel teeth, especially the teeth's front side, and enhances the running stability of the compressor.